COMUNITY STRUCTURE OF GASTROPOD ON MANGROVE FORESTS DESA LALANG KECAMATAN SUNGAI APIT KABUPATEN SIAK - Susanti, Rahmi; Efriyeldi, Efriyeldi; Nasution, Syafruddin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbstractThe class of gastropods is the largest class in Phylum Molluska. One of the habitat that is controlled by gastropod is mangrove forest. The structure of the gastropod community of phylum molluska is influenced by changes in environmental factors. This research was conducted in Lalang Village Sungai Apit Subdistrict Siak Regency, in March 2018. The purpose of this research is to know the structure of gastropod community which includes: type, density, diversity, uniformity, dominance, distribution pattern.To support the research data, also observed mangrove density and water quality in Lalang Village in Sungai Apit Subdistrict Siak Regency. Sampling using line transect method was done on 3 stations. 6 gastropod species found in mangrove forest area with the value of gastropod density obtained at each research station is 3.57-4.84 ind / m2. the value of its diversity ranges from 1.02-1.11. while the value of uniformity obtained is 0.48-0.62 and the dominance value ranged from 0.14 to 0.17. Gastropod distribution pattern is uniform, type of mangrove that is found is 6 species.Kata Kunci:Gastropoda, Comunity structure, Mangrove